2019
DOI: 10.3201/eid2505.181591
|View full text |Cite
|
Sign up to set email alerts
|

Severe Myasthenic Manifestation of Leptospirosis Associated with New Sequence Type ofLeptospira interrogans

Abstract: We report the rapid development of a myasthenic crisis as the first-time manifestation of myasthenia gravis. The symptoms developed in the course of acute leptospirosis associated with a new sequence type of Leptospira interrogans . Antibiotic treatment led to rapid amelioration of myasthenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Lrp4 MG patients are predominantly female (female to male ratio of 2.5:1) and have usually a generalized mild muscular weakness, unless additional antibodies to MuSK or AChR are present [48]. In an exceptional case, Lrp4 MG with severe muscle weakness manifested during infection with a new sequence isotype of Leptospira interrogans [49]. The role of the thymus in Lrp4 MG is unclear; one epidemiological study suggests the occasional presence of thymic hyperplasia [48].…”
Section: Clinical Aspects Of Myasthenia Gravismentioning
confidence: 99%
“…Lrp4 MG patients are predominantly female (female to male ratio of 2.5:1) and have usually a generalized mild muscular weakness, unless additional antibodies to MuSK or AChR are present [48]. In an exceptional case, Lrp4 MG with severe muscle weakness manifested during infection with a new sequence isotype of Leptospira interrogans [49]. The role of the thymus in Lrp4 MG is unclear; one epidemiological study suggests the occasional presence of thymic hyperplasia [48].…”
Section: Clinical Aspects Of Myasthenia Gravismentioning
confidence: 99%
“…Koneczny et al demonstrated for the first-time severe form of myasthenia gravis as a rare manifestation of acute leptospirosis. The authors isolated a new sequence type of L. interrogans as the causative agent [68].…”
Section: Infections and Autoimmunity During Auto12mentioning
confidence: 99%
“…Thus, several hypotheses may be raised. A first hypothesis points out molecular mimicry as a pathogenetic mechanism through which dysbiosis induces MG because of the reported case of MG onset after Leptospira interrogans acute infection [ 87 ]. In this view, the re-arrangement of intestinal flora would result in molecular mimicry phenomena underlying MG pathogenesis.…”
Section: Discussionmentioning
confidence: 99%